Enforced disappearances in Bangladesh and Women’s role: Does a woman become the new ‘Patriarch?’ - Ara, Yasmin (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2022.